Pengaruh Pendapatan, Luas Lahan, Lokasi Lahan dan Jenis Pekerjaan terhadap Keputusan Masyarakat Mengkonversi Lahan Pertanian Menjadi Lahan Non-Pertanian (Studi Kasus: Kecamatan Gambut, Kabupaten Banjar, Kalimantan Selatan) - Ramitayudha, Anisa (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This research aims to determine whether income, land area, land location, andthe type of work to people’s have significant effect simultaneously and partially to thepeople's decision to convert agricultural land into non-agricultural land in GambutSub-District and to know its impact on the welfare of the landowners. This research is quantitative, using primary data in the form of interviews with80 communities that have agricultural land in the Gambut Sub-District in 2016 until2017. The result of logit model regression shows that all variables have a significant effect simultaneously to people's decision to convert agricultural land into non-agricultural land in the Gambut Sub-District. In contrast, only partially significant influence is income and land area, where income and land area negatively affect the conversion rate of agricultural land. Different test results show that there is a marked difference between the income of the community before and after converting agrarianland. The average community income before converting agricultural land is moresignificant than after converting agricultural land.